2015
DOI: 10.1109/tim.2014.2376113
|View full text |Cite
|
Sign up to set email alerts
|

Metrological Characterization of a Signal Generator for the Testing of Medium-Voltage Measurement Transducers

Abstract: Nowadays, voltage transducers in medium-voltage (MV) distribution networks operate in nonsinusoidal conditions while their calibration is still based on simple sine-wave tests. A more significant characterization could be achieved using complex multitone signals. However, this requires an MV generator able to apply arbitrary voltage waveforms to the transducer under test. The authors have recently proposed a simple MV signal generator that can be effectively employed for this purpose. In this paper, the perfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(12 citation statements)
references
References 21 publications
0
12
0
Order By: Relevance
“…A two second time window (hence 100 fundamental periods) and 100 kHz sampling rate have been employed. The estimated FRF can be used to pre-filter the spectrum of the desired excitation signal, thus obtaining the signal v g to be applied at the input of the power amplifier [21], [22].…”
Section: Resultsmentioning
confidence: 99%
“…A two second time window (hence 100 fundamental periods) and 100 kHz sampling rate have been employed. The estimated FRF can be used to pre-filter the spectrum of the desired excitation signal, thus obtaining the signal v g to be applied at the input of the power amplifier [21], [22].…”
Section: Resultsmentioning
confidence: 99%
“…Its architecture resembled that of a voltage generator [7], [8] previously developed by the authors for the testing of medium voltage transducers; the architecture is shown in Fig. 7, while its block diagram is reported in Fig.…”
Section: Methodsmentioning
confidence: 99%
“…The fifth order simplified Volterra model recalled in the previous section has been used to represent the behavior of a CVT under test (TUT) having 0.5 accuracy class, 200V/100V voltage ratio and 20 VA rated burden. Its primary winding has been connected to an arbitrary voltage generator, similar to that described in [28], able to generate the proper voltage signals required by the tests. Primary and secondary winding voltages of the TUT has been collected by using two highaccuracy resistive dividers.…”
Section: Experimental Validation Of the Proposed Modelmentioning
confidence: 99%